Gamma-rays shielding and antibacterial properties of coated fabrics - OĞUZ, NACIYE SÜNDÜZ; KODALOĞLU, FEYZA AKARSLAN (The National Research and Development Institute for Textiles and Leather, 2023)
Today, with the development of technology, radiation exposure is more common. Therefore, alternative methods have been developed because shielding, which is used as the most effective method for radiation protection, has risks in terms of health. With the awareness of consumers, the use of antibacterial textile products has increased in terms of hygiene and comfort. In this study, for this purpose nano-silver which has antibacterial properties was applied to woven fabrics with the impregnation method and the fabrics were coated with tungsten and barium sulfate, which have radiation shielding properties. The radiation shielding properties of fabrics against 137 Cs source emitting γ radiation were investigated. In this study, woven fabrics with radiation protection and antibacterial properties, which are very important for the health sector, were obtained and compared with each other.